Azure Fabric: Microsoft's Unified Data Platform for the Enterprise - Vijaya Sekhar Godavarti, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines Microsoft's Azure Fabric, a revolutionary cloud-scale service transforming enterprise data management through unified storage and interface capabilities. It explores how Azure Fabric addresses the challenges of managing distributed data systems in modern enterprises by providing a comprehensive solution that integrates various data services into a single platform. The article encompasses the evolution of Microsoft's data platform, highlighting the transition from specialized solutions to a unified approach. It analyzes Azure Fabric's key features, including its unified storage architecture based on OneLake technology, role-optimized interface design, advanced integration capabilities, scalability features, and integrated governance framework. Furthermore, the article investigates the impact of Azure Fabric on enterprise data strategy, examining how the platform influences data consistency, skill optimization, cost efficiency, governance, and scalability. It demonstrates how Azure Fabric's unified approach enables organizations to streamline their data management infrastructure while maintaining robust security and governance features.
Keywords: Enterprise Data Management; Cloud Computing; Data Integration; Unified Platform; Data Governance